2020
DOI: 10.1111/jac.12476
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of alleviating early planting‐associated cold susceptibility of soybean using microbes: New insights from microbiome analysis

Abstract: Cold susceptibility is a concern when growing crops of tropical origin in temperate regions. Crops such as rice, corn, sorghum, and soybean are generally susceptible to chilling stress. From production standpoint, a crop's cold tolerance is particularly important when the general recommendation is to adopt earlier than currently practicing planting dates in the spring. Early planting is a potential route to increase soybean yield in the United States. Nonetheless, early planting is often not practically feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 130 publications
(164 reference statements)
0
5
0
Order By: Relevance
“…In our study, microbial communities associated with soybean growth had a dense microbial network structure which signifies a more complex interaction in the rhizosphere. Other studies reported that microbial network complexity characterizes the high-yield sites compared with the low-yield sites of soybean in the field (91). A non-random co-occurrence pattern inferred in the microbial network interaction indicates that seed treatment strains interact cooperatively with other key species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, microbial communities associated with soybean growth had a dense microbial network structure which signifies a more complex interaction in the rhizosphere. Other studies reported that microbial network complexity characterizes the high-yield sites compared with the low-yield sites of soybean in the field (91). A non-random co-occurrence pattern inferred in the microbial network interaction indicates that seed treatment strains interact cooperatively with other key species.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, microbial communities associated with soybean growth had a dense microbial network structure which signifies a more complex interaction in the rhizosphere. Other studies reported that microbial network complexity characterizes the high-yield sites compared with the low-yield sites of soybean in the field (91).…”
Section: Persistence Of the Seed-treated Sabbs And The Seed Treatment...mentioning
confidence: 97%
“…Although the global average temperature is increasing yearly and many studies have been conducted on the effects of high temperatures on crop production, the frequency and intensity of low temperature (LT) stress are undoubtedly increasing [5,6]. As a result, researchers in many nations have started to shed light on the influence of LT stress on the yield of crops, mainly the frequency and intensity of LT stress, which has had a significant impact on wheat production in Europe, North America, and China [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Soybean is a thermophilic plant, therefore the seeds are sown in warm soil to avoid low temperature stress. It is assumed that soil temperature below 10 • C adversely affects seed germination [3]. In turn, excessively delayed sowing may result in a decrease in yields, especially when drought occurs [4].…”
Section: Introductionmentioning
confidence: 99%